2015
DOI: 10.1080/15376494.2013.828808
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Mode of Martensite-Austenite Constituents Containing Multiphase Steel Controlled by Microstructural and Micromechanical Aspects

Abstract: The fracture mode in different M-A constituents containing multiphase steels under impact load was examined considering their microstructural and micromechanical aspects. The results showed that a ductile fracture develops in the fine-grained bainitic ferrite/M-A multiphase by microvoids initiation and coalescence, while cleavage develops in the coarse-grained polygonal ferrite/M-A multiphase by microcracks initiation and propagation, due to their diversities in morphologies of microstructural components and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The results presented in this paper are based on the theoretical and experimental studies on processing routes for structural high-strength low-alloy (HSLA) steel previously fulfilled by Ishikawa et al [71], Wang et al [35], Misra et al [17,18], Bhadeshia et al [32,33], and many other researchers. The novelty of this work is that it compared The obtained data showed that varying only the finish rolling temperature and increasing the post-rolling cooling rate could increase the yield strength of (Nb+V+Al)-microalloyed steel of S355 grade by about 30% from 390 to 544 MPa.…”
Section: Variation Of the Ductile-brittle Transition Temperature Depe...mentioning
confidence: 98%
See 1 more Smart Citation
“…The results presented in this paper are based on the theoretical and experimental studies on processing routes for structural high-strength low-alloy (HSLA) steel previously fulfilled by Ishikawa et al [71], Wang et al [35], Misra et al [17,18], Bhadeshia et al [32,33], and many other researchers. The novelty of this work is that it compared The obtained data showed that varying only the finish rolling temperature and increasing the post-rolling cooling rate could increase the yield strength of (Nb+V+Al)-microalloyed steel of S355 grade by about 30% from 390 to 544 MPa.…”
Section: Variation Of the Ductile-brittle Transition Temperature Depe...mentioning
confidence: 98%
“…The acicular ferrite is characterized by high-angle boundaries, which is beneficial for the hindering of crack propagation [34]. Under a certain cooling rate, the martensite/austenite (M/A) conglomerates also appeared in the structure contributing to steel strength [35]. The pearlite-free structures mentioned earlier could be formed in low-carbon structural steel using post-rolling AC, which suppresses the austenite→pearlite transformation [36,37].…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, the hardness and elastic modulus of the M/A constituent differ from the matrix's, resulting in uncoordinated displacement during the impact test deformation process. This will further increase the stress around the M/A constituents [19,22]; therefore, the M/A constituents in the CGHAZ tend to be the crack sources. Previous studies have indicated that toughness deteriorates upon increasing the M/A constituent content and size.…”
Section: Effect Of Heat Input On the Cghaz Impact Toughnessmentioning
confidence: 99%
“…1,[131][132][133][134][135][136] The excellent ductility and strength in TRIP steels is a result of deformation based conversion of RA (retained austenite) to the martensite phase. 1,[137][138][139][140][141][142][143][144][145] This transformation (on deformation) of phases is called TRIP effect. 1,146 Figure 11 presents the TRIP effect during tensile testing of a specimen.…”
Section: Transformation-induced Plasticity Steelsmentioning
confidence: 99%